Organizing Knowledge for Environmentally and Socially Sustainable Development: Proceedings of a Concurrent Meeting of the Fifth Annual World Bank Conference on Environmentally and Socially Sustainable Development - World Bank (Washington D.C. World Bank, 1998)
The book contains the Organizing Knowledge for Environmentally and Socially Sustainable Development.
gau 02/11/16
Loans